The Prognostic Value Of Hyponatremia In Children With Pneumonia Of Hospitalization Duration - يوسف , الهام; مأمون حكيم; محمد زاهر (Latakia University Journal -Medical Sciences Series, 2023)
Background: The occurrence of hyponatremia in children with pneumonia is associated with several disorders that increase morbidity and mortality and prolong hospitalization. Objectives: The prognostic value of hyponatremia in children with pneumonia of hospitalization duration . Methods: In a prospective, prognostic study that included 96 children with pneumonia, their ages ranged between 2 and 12 years, between March 2019 and for a period of one year. Recording their hospitalization period. Results: Serum hyponatremia was observed in 64 children out of 96 children, at a rate of 66.7%. A statistically significant relationship was found between hyponatremia and hospitalization period, p-value 0.01. Also, an inverse correlation was found between the child’s age and hospitalization period and a positive correlation between C-reactive protein indicator and duration of hospitalization. Conclusion: Hyponatremia is common in children with pneumonia and is associated with length of hospitalization, and the value of serum sodium can be relied upon as a prognostic factor for predicting length of hospitalization.